2017
DOI: 10.1080/10942912.2017.1288135
|View full text |Cite
|
Sign up to set email alerts
|

Detection of sulfonamide and tetracycline antibiotic residues in Turkish pine honey

Abstract: Pine honey is a honeydew honey that can be produced endemically in eastern Mediterranean. Turkey is the world's largest producer of pine honey with around 95% export share. Antibiotic residue in honey is still an important problem worldwide. The aim of this study was to determine sulfonamide and tetracycline group antibiotics in pine honey collected from Aegean Region of Turkey. For this purpose, 59 natural pine honey samples were detected by competitive enzyme-linked immunoassay method. Tetracycline group ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 10 publications
0
8
1
1
Order By: Relevance
“…Tetracycline were found in one (5.9%; out of 17) domestic honey samples and one (7.1%; out of 14) in imported honey samples in presented study. It is lower than reports from Turkey, 59% 8 and Greece, 29% 10 . Kasem-Saleh et al from Yemen reported that higher tetracycline were found in imported than in localy produced honey samples (55.5% in imported and 28.6% in domestic honey samples) 7 .…”
Section: Resultscontrasting
confidence: 59%
See 2 more Smart Citations
“…Tetracycline were found in one (5.9%; out of 17) domestic honey samples and one (7.1%; out of 14) in imported honey samples in presented study. It is lower than reports from Turkey, 59% 8 and Greece, 29% 10 . Kasem-Saleh et al from Yemen reported that higher tetracycline were found in imported than in localy produced honey samples (55.5% in imported and 28.6% in domestic honey samples) 7 .…”
Section: Resultscontrasting
confidence: 59%
“…ELISA technque were performed according to the manufactures instruction (Labtron Equipment, UK) by using Bio Scientific ELISA test kit for tetracycline. For test, 0.5 g of honey weighed into a centrifuge vial, 3.5 mL of 1x Phosphate Buffered Saline (PBS) added ensureing that the sample is fully dissolved in the PBS by heating for 5-10 minutes at 50 °C; vortexed for 10 minutes in a multi-tube vortexer or shaked 30 minutes on a shaker, centrifuged for 10 minutes at 4000 x g; 200 µL of the supernatant transferd to a new tube containing 300 µL of 1x PBS, vortexed for 1 minute and after that 75 µL per well used in the assay 8 . Sulfite-Reducing Anaerobic Bacteria: Detection of the sulfite-reducing anaerobic bacteria was carried out by the technique of enumeration in a solid medium in tubes.…”
Section: Determination Of Hydroxymethylfurfural (Hmf)mentioning
confidence: 99%
See 1 more Smart Citation
“…Honey has numerous uses and composes formulations of many pharmaceutical, cosmetic, and food products (Kumar, Gill, Bedi, & Kumar, 2018). In recent years, several reports claim the contamination of honey by antibiotics (Galarini, Saluti, Giusepponi, Rossi, & Moretti, 2015;Kivrak, Kivrak, & Harmandar, 2016;Korkmaz, Kuplulu, Cil, & Akyuz, 2017). The presence of antibiotic residues in honey represents a danger to the health of consumers due to the occurrence of allergic reactions, anaphylactic shocks in susceptible individuals, imbalance of intestinal flora, development of bacterial resistance, and the transfer of multi-resistance between bacteria by plasmid (Belas, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the authors point out that the presence of the highest concentrations found was in honeys from autumn blossoms, in which contamination of 18.5% of samples with gentamicin was found (Mahmoudi et al, 2014). Korkmaz et al (2017) evaluated 59 Turkish honey samples using an enzyme immunoassay to determine sulfonamides and tetracyclines. According to the data, the samples have a high level of contamination by these antibiotics, given that concentrations between 6 and 42 µg kg -1 of tetracycline were found in 35 samples and between 3 and 32 µg kg -1 of sulfonamides in 31 of the evaluated samples (Korkmaz et al, 2017).…”
mentioning
confidence: 99%